Mechanical stretch-induced vascular hypertrophy occurs through modulation of leptin synthesis-mediated ROS formation and GATA-4 nuclear translocation - Ghantous, Crystal M.; Kobeissy, Firas H.; Soudani, Nadia; Rahman, Farah A.; Al-Hariri, Mustafa; Itani, Hana A.; Sabra, Ramzi; Zeidan, Asad (Frontiers in Pharmacology, 2015)
Background: Obesity and hypertension are associated with increased leptin production contributing to cardiovascular remodeling. Mechanisms involving mechanical stretch-induced leptin production and the cross talk between signaling pathways leading to vascular remodeling have not been fully elucidated. Methods and results: Rat portal vein (RPV) organ culture was used to investigate the effect of mechanical stretch on leptin protein expression in vascular smooth muscle cells (VSMCs). Moreover, the involvement of reactive oxygen species (ROS), the RhoA/ROCK pathway, actin cytoskeleton dynamics and the transcriptional factor GATA-4 activation in mechanical stretch-induced vascular remodeling were investigated. Stretching the RPV for 1 hour or 24 hours significantly increased leptin protein level and ROS formation in VSMCs, which was prevented by 1 hour pretreatment with the ROCK inhibitor Y-27632 and the actin cytoskeleton depolymerization agent cytochalasin D. Moreover, Western blotting and immunohistochemistry revealed that mechanical stretch or treatment with 3.1 nmol/L leptin for 24 hours significantly increased actin polymerization, as reflected by an increase in the F-actin to G-actin ratio. Increases in blood vessels’ wet weight and [3H]-leucine incorporation following a 24 hour treatment with conditioned media from cultured stretched RPVs indicated RPV hypertrophy. This effect was prevented by 1 hour pretreatment with anti-leptin antibody, indicating leptin’s crucial role in promoting VSMC hypertrophy. As an index of GATA-4 activation, GATA-4 nuclear translocation was assessed by immunohistochemistry method. Pretreating VSMC with leptin for 1 hour significantly activated GATA-4 nuclear translocation, which was potently attenuated by the NADPH oxidase inhibitor apocynin, Y-27632, and cytochalasin D. Conclusion: Our results demonstrate that ROS formation, RhoA/ROCK pathway, and GATA-4 activation play a pivotal role in mechanical stretch-induced leptin synthesis leading to VSMC remodeling.